2010
DOI: 10.1080/14786410903281774
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a new monoterpenic ester from the leaves ofMichelia compressa(Maxim.) Sargent var.formosanaKanehira (Magnoliaceae)

Abstract: Pressafonin A (1) and pressafonin B (2), two new Michelia monoterpenic esters, have been isolated from Michelia compressa (Maxim.) Sargent var. formosana Kanehira (Magnoliaceae), and their structures are determined on the basis of spectroscopic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In previous studies, the compounds from Michelia compressa var. formosana have been reported [2,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the compounds from Michelia compressa var. formosana have been reported [2,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Eight known compounds were identified as caryolane-1,9 β -diol ( 2 ), clovane-2 α ,9 β -diol ( 4 ) [ 10 ], pressafonin A ( 6 ), pressafonin B ( 7 ) [ 13 ], oplodiol ( 8 ) [ 14 ], ent-oplopanone ( 9 ) [ 15 ], abscisic acid ( 10 ) [ 16 ] and (3 S ,5 R ,6 S ,7 E )-3,5,6-trihydroxy-7-megastigmen-9-one ( 11 ) [ 17 ] by comparison of their NMR spectroscopic data with those reported in the literature ( Supporting Information ).…”
Section: Resultsmentioning
confidence: 99%
“…Field observation in Changsha (China) indicated that its flowers started blooming in late March and continued into early May for about 50 days [ 2 ]. In the course of screening for biologically and chemically novel agents from Formosan Magnoliaceous plants [ 3 7 ], M. crassipes was chosen for further phytochemical investigation. The compounds derived from the stems include one oxoaporphine, liriodenine ( 1 ) [ 8 ]; four benzenoids, vanillic acid ( 2 ) [ 9 ], vanillin ( 3 ) [ 10 ], p -hydroxybenzoic acid ( 4 ) [ 10 ], and p -hydroxybenzaldehyde ( 5 ) [ 11 ]; two amides, N - trans -feruloyltyramine ( 6 ) [ 12 ] and N - cis -feruloyltyramine ( 7 ) [ 13 ]; one cyclitol, (–)-liriodendritol ( 8 ) [ 14 ].…”
mentioning
confidence: 99%